Fallow management increases habitat suitability for endangered steppe bird species through changes in vegetation structure. Issue 9 (1st July 2019) - Sanz‐Pérez, Ana; Giralt, David; Robleño, Irene; Bota, Gerard; Milleret, Cyril; Mañosa, Santiago; Sardà‐Palomera, Francesc
Abstract: In the face of the dramatic worldwide decline of farmland bird populations, the preservation of fallow fields is a conservation measure encouraged through subsidies (e.g. agri‐environmental schemes, AES). Beyond the general benefits of increasing fallow availability for endangered steppe bird populations, there is a lack of knowledge on how fallow management can contribute to meeting species‐specific habitat requirements. We used occurrence data from three steppe bird species protected at the EU level (Stone Curlew Burhinus oedicnemus, Little Bustard Tetrax tetrax and Calandra Lark Melanocorypha calandra ), framed in a quasi‐experimental approach covering an unprecedented spatio‐temporal scale that included 612 fallow fields over a 3‐year study period in an agricultural Mediterranean landscape (Spain). We used path analysis to explore the mechanisms by which common agricultural practices affected species‐specific occurrence. We examined partial effects of agricultural practices on vegetation structure and food availability, and the partial effect of these variables on bird occurrence compared to control fields (no agricultural practices applied). Agricultural practices had a significant effect on the presence of the three studied species. Through changes in the vegetation structure, Shredding + Herbicide and Tillage increased the occurrence of the Stone Curlew and Shredding increased the occurrence of the Little Bustard. The occurrence of Calandra Lark was mostly affected by landscape variables. Synthesis and applications. Our study highlights that, in addition to the acknowledged positive role of fallow availability, applying a limited number of specific agricultural practices before the breeding season can further increase bird occurrence by changing the vegetation structure. Using path analysis, we explored the mechanisms driving the occurrence of three steppe bird species under different agricultural practices. Such information is key to providing specific recommendations for future conservation management of endangered species within agri‐environmental schemes. Abstract : Our study highlights that, in addition to the acknowledged positive role of fallow availability, applying a limited number of specific agricultural practices before the breeding season can further increase bird occurrence by changing the vegetation structure. Using path analysis, we explored the mechanisms driving the occurrence of three steppe bird species under different agricultural practices. Such information is key to providing specific recommendations for future conservation management of endangered species within agri‐environmental schemes. Foreign Language Abstract Resumen: Los ecosistemas agrícolas están sufriendo una gran pérdida de biodiversidad en las últimas décadas, siendo las poblaciones de aves esteparias uno de los grupos más afectados. La presencia de barbechos juega un papel clave para estas aves y por lo tanto es promovida por medidas agroambientales, donde los agricultores reciben subsidios por dejar tierras fuera de producción. Aunque estudios previos hayan descrito el efecto positivo de la presencia de tierras en barbecho, existe muy poca información sobre cómo hay que gestionar dichas parcelas para alcanzar las condiciones óptimas para estas especies. En este estudio evaluamos el efecto que tienen distintas prácticas agrícolas (e.g. labrado), en la presencia de tres especies de aves esteparias amenazadas (alcaraván, sisón y calandria) durante tres años. Utilizamos un diseño cuasi‐experimental que engloba 612 parcelas en barbecho situadas en el noreste de España. Mediante la técnica de "path analysis" examinamos el efecto parcial de las prácticas agrícolas en la estructura vegetal (e.g. cobertura) y disponibilidad de alimento (e.g. disponibilidad foliar), y el efecto parcial de estas variables en la presencia de aves en comparación con campos en control (sin gestionar). La presencia de las tres especies se vio beneficiada por distintas prácticas agrícolas. A través de cambios en la estructura vegetal, el picado con herbicida y el labrado beneficiaron la presencia del alcaraván y el picado benefició la presencia de sisón. Más allá del reconocido impacto positivo de las tierras en barbecho, nuestro estudio explica los mecanismos que promueven la presencia de aves esteparias amenazadas en barbechos y destaca los beneficios de aplicar una gestión controlada antes de la época de reproducción. Esta información es esencial para aportar recomendaciones específicas para cada especie y para maximizar la eficiencia y rentabilidad de medidas de conservación genéricas como las agroambientales.